Association of socio-demographic factors, perinatal characteristics, and hospital maternity practices with breastfeeding outcomes in the UAE - Taha, Zainab; Ktaibi, Farid El; Hijazi, Rafiq (Frontiers in Pediatrics, 2025)
Breastfeeding (BF) rates remain suboptimal in the United Arab Emirates (UAE), despite global and national efforts. This study examined the association of socio-demographic factors, perinatal characteristics, and hospital maternity practices with breastfeeding outcomes in the UAE. In this cross-sectional study, 1,815 participating mothers with children below the age of 2 answered structured questions related to socioeconomics, hospital practices, and BF. Multivariate analysis showed that a non-Emirati nationality and vaginal birth were significantly associated with higher initiation rates (AOR = 6.19, 95% CI 1.96–19.54 and AOR = 2.65, 95% CI 1.35–5.21, respectively), timely initiation (AOR = 0.48, 95%CI 0.35–0.66, respectively), longer BF duration (AOR = 1.55, 95%CI 1.05–2.27 and AOR = 1.45, 95%CI 1.08–1.93, respectively) and longer exclusive BF duration (AOR = 1.50, 95%CI 1.06–2.11 and AOR = 1.35, 95%CI 1.03–1.78, respectively). Additionally, parity, hospital practices, maternal education, and employment were significantly associated with certain BF practices. The findings support continued efforts to implement WHO's baby-friendly initiative in more hospitals in Abu Dhabi and also emphasize the importance of early and continuous antenatal education. Emirati mothers should be prioritized in these efforts as their BF practices need more attention. As maternal employment negatively influences breastfeeding duration, supportive measures such as extended maternity leave, designated expressing facilities in the workplace, and shorter working hours are crucial to promote continued breastfeeding among employed mothers.